PENINGKATAN HASIL BELAJAR PJOK DENGAN MENERAPKAN METODE INKUIRI - Lindawaty, Lindawaty (JURNAL PENA EDUKASI, 2019)
Abstract: The level of student mastery learning has increased quite encouraging, before the action was taken only 18 people (37.50%) only students who completed, but in the first cycle the level of completeness became 66.67% (32 people completed from 48 students). Furthermore in the second cycle the level of student mastery learning rose to 87.50%. The activeness of students in participating in the PJOK learning after the actions were taken in the first cycle and second cycle increased. There was an encouraging change in the activities of students, after the frequency of students' attendance was done well. The percentage of attendance in the first cycle is 90% and in the second cycle increases to 98.25%. Students are motivated to study independently and do research work in the field (laboratory). Keywords: Learning Outcomes, Inquiry Method Abstrak: Tingkat ketuntasan belajar siswa pun telah terjadi peningkatan yang cukup menggembirakan, sebelum dilakukan tindakan hanya 18 orang (37,50 %) saja siswa yang tuntas, tetapi pada siklus I tingkat ketuntasan menjadi 66,67 % (32 orang yang tuntas dari 48 siswa). Selanjutnya pada siklus II tingkat ketuntasan belajar siswa naik menjadi 87,50 %. Keaktifan siswa dalam mengikuti pembelajaran PJOK setelah dilakukan tindakan baik pada siklus I dan siklus II semakin meningkat. Terjadi perubahan yang menggembirakan terhadap aktifitas siswa, setelah dilakukan tindakan frekuensi kehadiran siswa samakin baik. Prosentase kehadiran pada siklus I adaalah 90 % dan pada siklus II naik menjadi 98,25 %. Para siswa termotivasi untuk belajar secara mandiri dan melakukan kerja penelitian di lapangan (laboratorium). Kata kunci: Hasil Belajar, Metode Inkuiri